2018
DOI: 10.1186/s13075-018-1744-3
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of C5a in the progression of experimental arthritis with Porphyromonas gingivalis infection in SKG mice

Abstract: BackgroundEpidemiological evidence to suggest that periodontal disease (PD) is involved in the progression of rheumatoid arthritis (RA) is increasing. The complement system plays a critical role in immune responses. C5a has been implicated in chronic inflammatory diseases, including PD and RA. Porphyromonas gingivalis is the major causative bacteria of PD and can produce C5a. Therefore, it is hypothesized that P. gingivalis infection is involved in the progression of RA by elevating C5a levels. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 53 publications
3
32
1
Order By: Relevance
“…All animal experimental procedures employed in this study were approved by the Ethical Committee of Hiroshima University (approved No. A16-33) and performed as previously reported [16]. Briefly, SKG mice were maintained under SPF condition until inoculation of bacteria and feces.…”
Section: Generation Of Pg-infected Experimental Arthritis Mouse Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…All animal experimental procedures employed in this study were approved by the Ethical Committee of Hiroshima University (approved No. A16-33) and performed as previously reported [16]. Briefly, SKG mice were maintained under SPF condition until inoculation of bacteria and feces.…”
Section: Generation Of Pg-infected Experimental Arthritis Mouse Modelmentioning
confidence: 99%
“…We previously showed that systemic or oral Pg administration exacerbated RA-like experimental arthritis in a mouse model [15,16]. Specifically, with systemic Pg infection, bacterial proteins were detected in swelling joint tissues [15].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations